Effects of Vermicompost on Soil and Plant Health and Promoting Sustainable Agriculture - Oyege, Ivan; Balaji Bhaskar, Maruthi Sridhar (Soil systems, 2023)
This review highlights the potential of vermicompost and its derived products as sustainable and eco-friendly solutions for enhancing production and pest management in grain crops. It assesses their impact comprehensively on crops such as maize, wheat, barley, rice, and pearl millet. Vermicompost improves soil quality, increases nutrient availability, boosts crop productivity, and enhances pest and disease tolerance. It acts as an organic fertilizer, enriching the soil with essential nutrients, humic acids, growth-regulating hormones, and enzymes, improving plant nutrition, photosynthesis, and overall crop quality. Furthermore, vermicompost shows promise in mitigating soil degradation and sequestering organic carbon while demonstrating the potential for pest management, including effectiveness against pests like fall armyworm (Spodoptera frugiperda). This review emphasizes the importance of integrated nutrient management and proper application strategies to maximize the benefits of vermicompost in grain crops. Factors such as the form and timing of application, efficacy against specific pests, and economic viability for different farming scales are discussed. Understanding these factors is crucial for successfully implementing and adopting vermicompost-based pest management strategies in grain crops. This review also explores the potential of vermicomposting as an eco-friendly and cost-effective solution to remediate organic contaminants, emerging contaminants, personal-care and pharmaceutical products, and microplastics. The review further identifies knowledge gaps and highlights the need for future studies to effectively utilize vermicompost and its derived products in cereal production for sustainable agriculture, contributing to global food security.